Analysis of the fresnel breakdown and diffraction losses across a hilly terrain region - Thaisa Jawhly (Discover Electronics)
Abstract A propagation loss analysis across a hilly terrain region is presented, with a focus on analyzing and modeling signal breakdown distances and signal losses in both line-of-sight (LOS) and non-line-of-sight (NLOS) scenarios. A generalized Fresnel breakdown relation dependent on the elevation angle for a hillslope is presented, which significantly scales down the breakdown distance with increased elevation angle and transmission frequency. For calculating propagation losses across the far field, it is inferred that the single terrain-obstructed losses are the sum of the free-space path loss and the knife-edge diffracted losses, calculated using the ITU-R P.526-15 recommendations. In addition, line-of-sight (LOS) probability is calculated by adopting the methods given in ITU-R P.1410-6. The proposed breakdown across the hillslope showed a reduction in breakdown distance compared to the standard breakdown estimates, which occur at 178 m away from the transmitter. This breakdown distance agrees well with measurement data. Furthermore, the International Telecommunication Union (ITU) recommendations and knife-edge diffraction model agreed fairly with the measurement data. The RMSE error for the proposed NLOS model fit was 9.56 compared to 9.21 for the measurement data fit, while that of the total loss (NLOS and LOS) was 13.92 compared to 12.56 for the measurement data fit. The proposed models explain 94% variability of the total losses while accounting for 69% of the NLOS losses.